Heterogeneous effects of foreign aid on local economic development - Jürgen Bitzer; Bernhard Christopher Dannemann; Erkan Gören (University of Oldenburg, Department of Economics, 2024)
We investigate the heterogeneity of the impact of World Bank foreign aid projects on local economic development across countries, sectors and time. Using a grid-cell dataset of geo-referenced aid data, satellite night-time light imagery, and climatic and socio-economic controls, we employ a difference-in-differences approach and an event-study design to estimate causal effects. Based on our grid-cell-level dataset, which includes 60,677 grid-cells in 133 countries and covers the period from 1992 to 2020, resulting in about 1.76 million grid-by-year observations, we find substantial heterogeneity in the effects of foreign aid on local economic development across countries, sectors, and time. These results suggest that the sample composition in terms of countries and sectors included explains in part the observed heterogeneity in the results on the impact of foreign aid on economic development.
Keywords: C23; F35; O10; O20; O40; R10; 330; Aid Effectiveness; Geo-Referenced Aid Projects; Economic Development; Economic Growth; Grid-Cell Analysis; GIS Data; Satellite Night-Time Light Data